Gastrointestinal involvement in granulomatosis with polyangiitis and microscopic polyangiitis: histological features and outcome - Latus, Joerg; Koetter, Ina; Fritz, Peter; Kimmel, Martin; Biegger, Dagmar; Ott, German; Stange, Eduard F.; Amann, Kerstin Ute; Alscher, Dominik M.; Braun, Niko (International Journal of Rheumatic Diseases, 2014)
Gastrointestinal (GI) involvement in patients with granulomatosis with polyangiitis (GPA) or microscopic polyangiitis (MPA) is rare.Medical charts of seven patients with GPA and MPA and GI involvement were reviewed regarding clinical presentation, outcome, diagnostic tools and therapy. Second, the cellular composition of the inflammatory infiltrate associated with the vascular lesions in histological samples (ileum, colon, rectum, duodenum) were investigated to identify possible treatment targets. Immunohistochemistry was done with antibodies against CD20, CD3 and CD34. Samples from a healthy control group (n = 15) were used for comparison.Mean age at onset of the first symptoms of vasculitis was 48 ± 21.3 years. At time of diagnosis GI symptoms were present in five out of seven patients (71%) and occurred during relapse of the vasculitis in two patients (29%). All patients had abdominal pain, four of seven (57%) had an acute kidney injury and three patients required renal replacement therapy. At the time of diagnosis five of seven patients (71%) required surgery and mean Birmingham Vasculitis Activity Score (BVAS) on admission was high (26.3 ± 7.7). Regarding outcome, one patient died due to gastrointestinal bleeding. Histological analysis showed significantly higher expression of CD3 in this patient compared to the control group (P = 0.02). Analysis of expression of CD20 and CD34 showed no statistically significant differences between patients with GPA and MPA with GI involvement compared to the control group.GI involvement in GPA and MPA is rare. Therapy directed at T cells might be an alternative treatment option.
EVALuna2:25467